Incidence and predictors of loss to follow-up among Ethiopian children on antiretroviral therapy: a systematic review and meta-analysis - Molla Yigzaw Birhanu; Getamesay Molla Bekele; Getasew Yirdaw; Bekele Simegn Demissie; Genanew Kassie Getahun; Selamawit Shita Jemberie (BMC Public Health, 2024)
Abstract Introduction Loss of follow-up (LTFU) from ART regular follow-up is one of the key acknowledged causes for the development of ART-resistant virus strains currently. It becomes a major weakness for the successful implementation of HIV care and treatment programs mainly in Sub-Saharan Africa but also globally. About 20—40% of children on ART loss their regular ART follow-up annually. Because of the inconsistency of the prior publications' findings, policymakers, programmers, and healthcare providers find it difficult to intervene. Hence, this study was conducted to provide a pooled incidence and identify the predictors of LTFU among children on ART in Ethiopia. Methods Articles were searched from PubMed/ MEDLINE, CINAHL, EMBASE, Google Scholar, and Science Direct, as well as organizational records and websites. This review included both retrospective and prospective follow-up studies published in English. The data were extracted using Microsoft Excel and exported into Stata™ Version 17.0 for further processing and analysis. The presence of heterogeneity was assessed using forest plots with the I2 test. To identify the source of heterogeneity subgroup analysis, meta-regression, publication bias, and sensitivity analysis were computed. The pooled incidence of LTFU was estimated using a random effects meta-analysis model with the DerSimonian-laired method. To identify the predictors, a 95% confidence interval with relative risk was used to declare the presence or absence of an association. Results In this systematic review and Meta-analysis, nine studies with a total of 3336 children were included. The pooled incidence of LTFU from ART was 5.83 (95% CI: 3.94, 7.72) per 100 children-years of observation with I2: 83% & p-value < 0.001. Those children who were from rural were had a 1.65 (95% CI: 1.06, 2.52) times higher chance of getting LTFU when compared with their counterparts. Children who had poor ART adherence had a 2.03 (95% CI: 1.23, 3.34) times higher chance of experiencing LTFU of ART than children having good ART adherence. Conclusions Among Ethiopian children on ART, one out of 167 had the risk of experiencing LTFU. Being rural dwellers and having poor ART adherence were the identified predictors of LTFU. Close follow-up and phone message text should be used to have good ART adherence among rural dwellers to meet the predetermined goal of ART.